Prinsip-Prinsip Komunikasi Islam dalam Dakwah Digital: Pendekatan Syariah untuk Pengembangan Regulasi Media Sosial - Batubara, Jihan Afri; Sazali, Hasan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Digital media plays a highly significant role in spreading Islamic da'wah in the modern era. One of the key aspects of digital da'wah is the application of Islamic communication principles, which serve as guidelines for conveying Islamic values through digital platforms, particularly social media. This study aims to analyze the application of Islamic communication principles in digital da'wah and how these principles can serve as a foundation for developing regulations and policies for social media. This research employs a qualitative approach with a literature study method as the primary technique, relying on written sources such as books and journals to explore Islamic communication principles and their application in digital da'wah activities. The findings indicate that Islamic communication principles, such as qoulan sadida, qoulan ma’rufa, qoulan maisuro, qoulan karima, qoulan baligha, and qoulan layyina, are highly relevant in regulating communication on social media. These findings suggest that implementing these values can help reduce hate speech, enhance ethical awareness in digital media, and strengthen a more polite and constructive digital da'wah.